Biological recovery of phosphorus from waste activated sludge via alkaline fermentation and struvite biomineralization by Brevibacterium antiquum - SEMERCİ, NESLİHAN (My University, 2022)
Struvite biomineralization is a promising method for phosphorus recovery from wastewater treatment plant streams, and the growth of responsible microorganisms in mixed cultures is one of the most critical points for applying this process in pilot and full-scale. This study aimed to investigate the growth and bio-struvite production of Brevibacterium antiquum in mixed sludge culture. Alkaline fermentation was applied at different pH conditions to enhance the phosphorus content of sludge for an efficient recovery, and pH 8 was determined as the most feasible considering the phosphorus release and sludge characteristics. Growth optimization studies showed that NaCl\"s presence decreases the growth rate of Brevibacterium antiquum and bio-struvite production. At the same time, pH in the range of 6.8-8.2 did not alter the growth significantly. In addition, studies showed the ability of Brevibacterium antiquum in unsterilized fermented sludge centrate to grow and recover the phosphorus as struvite. Thus, our results indicated the potential of struvite biomineralization in full-scale wastewater treatment plants.
Keywords: Yaşam Bilimleri; Biyoteknoloji; Temel Bilimler; Life Sciences; Biotechnology; Natural Sciences; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; Mikrobiyoloji; Yaşam Bilimleri (LIFE); BIOTECHNOLOGY & APPLIED MICROBIOLOGY; MICROBIOLOGY; Life Sciences (LIFE); Applied Microbiology and Biotechnology; Molecular Medicine; Biomineralization; Brevibacterium antiquum; Struvite; Phosphorus recovery; Alkaline fermentation; SP NOV.; ANAEROBIC FERMENTATION; BIO-STRUVITE; RELEASE; MECHANISM; PH; PHOSPHATE; DIGESTERS; GROWTH; Biomineralization; Brevibacterium antiquum; Struvite; Phosphorus recovery; Alkaline fermentation